DECONFLICTING WIND-OPTIMAL AIRCRAFT TRAJECTORIES IN NORTH ATLANTIC OCEANIC AIRSPACE - Rodionova, Olga; Delahaye, Daniel; Sridhar, Banavar; Ng, Hok K. (HAL CCSD, 2016)
International audience North Atlantic oceanic airspace accommodates more than 1000 flights daily, and is subjected to very strong winds. Flying wind-optimal trajectories yields time and fuel savings for each individual flight. However, when taken together, these trajectories induce a large amount of potential enroute conflicts. This paper analyses the detected conflicts, figuring out conflict distribution in time and space. It further describes an optimization algorithm aimed at reducing the number of conflicts for a daily set of flights on strategic level. Several trajectory modification strategies are discussed, followed with simulation results. Finally, an algorithm improvement is presented aiming at better preserving the trajectory optimality